THE ULTRASTRUCTURE OF THE CAT MYOCARDIUM : II. Atrial Muscle - McNutt, N. Scott (The Rockefeller University Press, 1969)
The ultrastructure of the cells specialized for contraction in the atrium and ventricle of young adult cats are compared. The cells specialized for conduction are not included. In addition to possessing distinctive atrial granules, the cells of the atrium are smaller in diameter (5–6 µ) than ventricular cells (10–12 µ) and have strikingly fewer T tubules. These latter differences are discussed in terms of their possible significance for the rate of conduction of the action potential. It is suggested that the very small number of T tubules in atrial cells may compensate for the small cell diameter, and thus permit rapid conduction of the action potential across the surface of the atrium. Coated dense vesicles found in association with the sarcoplasmic reticulum at the level of the Z line in ventricular muscle are more evident in atrial cells. In the virtual absence of T tubules in atrial cells, the sub-sarcolemmal cisternae of the sarcoplasmic reticulum are almost exclusively at the cell periphery. The ends of the cells and their processes in ventricular muscle are rectilinear with the interdigitated portions of the intercalated discs oriented transversely, whereas those of the atrium are often oblique to the myofilament axis. This difference may be related to the lower mechanical tension on atrial cells.